Mechanics of penta-graphene with vacancy defects under large amplitude tensile and shear loading. (14th April 2021) - Han, Tongwei; Wang, Xueyi; Zhang, Xiaoyan; Scarpa, Fabrizio; Tang, Chun
Abstract: Penta-graphene is a new two-dimensional metastable carbon allotrope composed entirely of carbon pentagons with unique electronic and mechanical properties. In this work we evaluate the mechanical properties of new classes of defective penta-graphene (DPG) subjected to tensile and shear loading by using molecular dynamics simulations. The types of defects considered here are monovacancy at either 4-coordinated C1 site or 3-coordinated C2 site, and double vacancy (DV). We focus in particular on the effects of the different topologies of defects and their concentrations on the elastic constants and the nonlinear mechanics of this allotropic form of carbon. The results indicate that DPG has a plastic behavior similar to pristine penta-graphene, which is caused by the irreversible pentagon-to-polygon structural transformation occurring during tensile and shear loading. The tensile and shear moduli decrease linearly with the concentration of defects. Monotonic reductions of the tensile yield and shear stresses are also present but less pronounced, while the yield strains are unaffected. Penta-graphene with 4-coordinated and DVs feature a change of the Poisson's ratio from negative to positive when the defect concentration rises to about 3% and 6%. Temperature can trigger structural reconstruction for free-standing DPG. The critical transition temperature increases due to the vacancy defects and the defects can delay the structure transition. These findings are expected to provide important guidelines for the practical applications of penta-graphene based micro/nano electromechanical systems.